Boom and Bust and Sovereign Ratings - Reisen, Helmut (OECD Development Centre Working Papers, 1999)
The 1990s have witnessed pronounced boom-bust cycles in emerging-markets lending, culminating in the Asian financial and currency crisis of 1997-98. By examining the links between sovereign credit ratings and dollar bond yield spreads over 1989-97, this paper aims at broad empirical content for judging whether the three leading rating agencies - Moody's, Standard ' Poor's and Fitch IBCA - can intensify or attenuate boom-bust cycles in emerging-market lending. First, an event study exploring the market response for 30 trading days before and after rating announcements finds a significant impact of imminent upgrades and implemented downgrades for a combination of ratings by the three leading agencies, despite strong anticipation of rating events. Second, a Granger causality test, by correcting for joint determinants of ratings and yield spreads, finds that changes in sovereign ratings are mutually interdependent with changes in bond yields. These findings are based on many more ...